Bimaxillary Orthognathic Surgery in Skeletal Class III Malocclusion - Stephanus Christianto; Yiu Yan Leung (Faculty of Dentistry, Universitas Trisakti, 2019)
Background: Skeletal Class III malocclusions can vary in severity, with different levels of treatment available to reflect this variance. In cases of moderate to severe skeletal discrepancy, orthodontic treatment in conjunction with orthognathic surgery is a common treatment option. This case report outlines an orthosurgical treatment approach for a patient with severe skeletal Class III malocclusion. Case Report: A 23-year-old female presented with skeletal Class III malocclusion. Pre-surgical orthodontic treatment was done after 1.5 years. The lateral profile view showed a concave profile, incompetent lip closure, deficiency in paranasal area, acute nasolabial angle, and obtuse labiomental fold. Intraorally, she had a negative 5.5 mm overjet and 2 mm overbite. The surgical procedures performed included high-level Le Fort I osteotomy, bilateral intraoral vertical ramus osteotomies (IVRO), and genioplasty. Conclusion: The treatment of skeletal Class III dentofacial deformity should be planned according to the malocclusion and facial profile to achieve a functional and esthetic outcome. A systematic treatment plan that takes into consideration the patient’s expectations and concerns must be created and implemented for a satisfactory outcome.